A 'sustainability window' of urban form. (June 2016) - Lohrey, Steffen; Creutzig, Felix
Highlights: Climate change, air pollution and congestion become key issues for cities worldwide. We investigate how urban form and transport system modify sustainability objectives. We design an urban economics model and compare the results with empirical data. A sustainable window identifies the sweet spot of urban form. A minimal urban density of 50 persons/ha realizes sustainability objectives. Abstract: With global environmental change and the rise of global megacities, environmental and social externalities of urban systems, and especially of urban form, become increasingly prevalent. The question of optimal urban form has been debated and investigated by different disciplines in numerous contexts, including those of transport costs, land consumption and congestion. Here we elucidate theoretically how urban form and the urban transport system systematically modifies sustainability concerns, such as greenhouse gas emissions, local air pollution and congestion. We illustrate our analytical considerations with empirical analysis. Denser urban form would almost unambiguously mitigate climate change, but it would also lead to undesired effects, such as a higher proportion of urban dwellers affected by air pollution. Our study presents a 'sustainability window' by highlighting trade-offs between these sustainability concerns as a function of urban form. Only a combination of transportation policies, infrastructure investments and progressive public finance enables the development of cities that perform well in several sustainability dimensions. We estimate that a residential population density between 50 and 150 persons/ha and a modal share of environmental modes above at least 50% corresponds to the sustainability window of urban form. The parameters of the sustainability window of urban form is subject to policy changes and technological progress.